The Location and Employment Choices of New Firms: An Econometric Model with Discrete and Continuous Endogenous Variables - Carlton, Dennis W. (The Review of Economics and Statistics, 1983)
Dennis W. Carlton, The Location and Employment Choices of New Firms: An Econometric Model with Discrete and Continuous Endogenous Variables, The Review of Economics and Statistics, Vol. 65, No. 3 (Aug., 1983), pp. 440-449